2020
DOI: 10.1080/15287394.2020.1830457
|View full text |Cite
|
Sign up to set email alerts
|

Hand-to-mouth and other hand-to-face touching behavior in a quasi-naturalistic study under controlled conditions

Abstract: Data gaps exist in our understanding of hand-to-mouth touching behavior among adults, despite its relevance for accurately characterizing inadvertent ingestion exposures to chemical and pathogenic microbial agents and consequent associated health risks. The present study describes detailed observations of the frequency and nature of hand-to-mouth and other hand-to-face touching behavior among 14 male and female volunteers in a controlled, quasi-naturalistic setting. Participants performed four 15-min tasks: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…The average CF of HFC in this study was higher than those reported in previous studies: 23/person/hr [ 4 ], and 15.7/person/hr [ 5 ], 9.5/person/hr [ 9 ], and 2.6/person/hr [ 10 ]; however, our results are consistent with the finding of 27.7 (6-49)/45 min of another study [ 12 ]. The most frequently encountered non-mucous membrane and mucous membrane HFC areas in this study were the head and the mouth, nose, and eyes, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The average CF of HFC in this study was higher than those reported in previous studies: 23/person/hr [ 4 ], and 15.7/person/hr [ 5 ], 9.5/person/hr [ 9 ], and 2.6/person/hr [ 10 ]; however, our results are consistent with the finding of 27.7 (6-49)/45 min of another study [ 12 ]. The most frequently encountered non-mucous membrane and mucous membrane HFC areas in this study were the head and the mouth, nose, and eyes, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…This was a pilot study to describe the frequency, duration, and intensity of HFC however, our results were consistent with 27.7(6-49)/45 min of the other study [12]. The most frequently encountered non-mucous membrane and mucous membrane HFC areas identified in this study were the head, and the mouth, nose, and eyes, respectively.…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 89%
See 2 more Smart Citations
“…Viruses readily transfer from contaminated surfaces to the hand upon contact [19][20][21] and from hands to the mucous membranes on the face [21][22][23] . People touch their faces frequently, with studies reporting average handto-face contacts ranging from 16 to 37 times an hour [24][25][26] . Taken together, this suggests surface contamination could pose a risk for indirect SARS-CoV-2 transmission, similar to other respiratory viruses 8 .…”
Section: Introductionmentioning
confidence: 99%